The performance of the MalaysianDRG Casemix System and financial implications of inaccurate documentation and coding error - Saizan, Sarah (2021)
Introduction: The Ministry of Health (MOH) implemented the MalaysianDRG casemix system in 2010, yet its achievement has not been studied. To date, there have been no other study on the performance of the MalaysianDRG casemix system in MOH hospitals. Therefore, its performance cannot be determined and benchmarked against other casemix system elsewhere, thus hindering future improvement initiatives. Objectives: There were three study objectives; 1) to describe the trend of the MalaysianDRG casemix performance in MOH hospitals from 2017-2018, 2) to explore factors contributing to poor casemix performance in a MOH hospital and, 3) to determine the financial implications due to inaccurate documentation and coding error Methodology: This study consisted of two parts. Part 1 utilized a sequential explanatory mixed method design to answer the first and second study objectives. It began with a cross-sectional study using secondary data to describe the trend of casemix performance according to national target indicators in five MOH hospitals in Malaysia. Multistage sampling was applied in selecting five hospitals representing five regions in Malaysia. All casemix audit reports between 2017 to 2018 in each hospital were analysed descriptively. The performance of the four national target indicators were presented for each hospital. To further understand the factors of poor casemix performance, a case study was conducted at the hospital with the lowest casemix performance. Data collection was carried out using in-depth-interviews, observation, and document reviews, and were analysed using thematic analysis. Part 2 of the study involved a cross-sectional study using secondary data of 226 audit and re-audit forms oftwo MOH hospitals which underwent re-audit by the Casemix Unit, MOH in 2017. The data collection involved obtaining old and new codes from the reaudit forms to be entered in the MalaysianDRG casemix costing module to produce a specific Diagnosis Related Group (DRG) and Cost Group Weight (CGW). The CGW was multiplied by the latest National Base Rate 2016 to derive the price per case (PPC) for each DRG. A descriptive cost analysis was conducted to measure financial implications before and after the re-coding process in the re-audits. The statistical differences in PPC were measured using paired sample t-test. Results: All five hospitals achieved the targets for the third and fourth indicators pertaining to coding accuracy in main and other condition. However, four hospitals achieved below the intended targets for the accuracy in documentation of main condition, and completeness in documentation of other condition. Thematic analysis of the case study discovered four themes with 14 subthemes detailing the factors contributing to poor casemix performance at Hospital E. The themes were poor organizational commitment, resource management issues, information system failure, and poor stewardships in leading casemix initiatives. The final part of the study revealed the difference in costs of RM227,657 due to inaccurate clinical documentation and RM 68,216 for coding error. The differences between mean (SD) cost per case of the original vs. new codes due to inaccurate clinical documentation [RM10,208.19(12273) vs. RM11,244.53(13785.27), p<0.05], and coding error [RM10,208.19(12273.04) vs. RM11,215.52(13798.03) p<0.05] were statistically significant. Conclusion: It can be concluded that even though the performance of the MalaysianDRG casemix system in MOH hospitals is moderate, the trend of the national target achievements is showing positive signs of improvement. The MalaysianDRG casemix system is the way forward in hospital management and if utilized optimally, may yield great financial benefits to MOH. However, before this can be achieved, factors that hamper its success and flaws that result in costly financial implications must be overcome. The study findings may be used to spread awareness and formulate targeted solutions towards future excellence in the MalaysianDRG casemix system.